Oliveramine: An Isolated Alkaloid from Fagraea fragrans (Tembesu) Bark - Dasril Basir; Jefri Liasta; Annisa Amelia; Miksusanti Miksusanti; Susilawati Susilawati (Jurnal Kimia Sains dan Aplikasi, 2022)
This paper described the progress of phytochemical, especially alkaloids, work on Fagraea fragrans species (tembesu), Loganiaceae. A dimeric-pyridine alkaloid with molecular formula C20H20O4N2 has been successfully isolated from diethyl ether extracts from this plant’s barks. The alkaloid was explored from diethyl ether extracts using sulphuric acid (2%), then basified with ammonium hydroxide (25%) until the solution had a pH of 10.5. The later solution was extracted again with chloroform. The alkaloid residue was subjected to column chromatography and eluted with 10% acetone in chloroform. The chemical structure of the isolated dimeric-pyridine alkaloid was determined by LCMS/MS, 13C-NMR, and 1H-NMR spectroscopies. As a result, the isolated dimeric-pyridine alkaloid was closely similar to the oliveramine alkaloid, and this is also the first report about oliveramine from Fagraea fragrans (F. Fragrans).